Countries of the Eurasian Economic Union in the Global Economy - Nikolay I. Didenko; Ekaterina S. Romashkina (Модернизация, инновация, развитие, 2017)
Purpose: the aim of the paper was to assess the level of involvement of the Eurasian economic Union (hereinafter EAEC) into the global economy. Methods: methods of system and synthesis analysis, structural-logical, economic-statistical, comparative and retrospective analysis were used in the study. Results: the structure of the global economy as a range of functional subsystems was presented. The indicators of involvement of countries into the global economy for each functional subsystem were suggested. The levels measuring the range of involvement of the country in global economy for each functional subsystem were proposed. The level of engagement of Armenia, Belarus, Kazakhstan, Kyrgyzstan, Russia into the global economy for each functional subsystem was assessed. The value of the levels of involvement of the EAEC countries were summarized in the table. Conclusions and Relevance: the EAEC countries are characterized by a low level of involvement in the global economy for most of the functional subsystems. The greatest number of lowest values were concentrated in such subsystems as the global transnational production and the global monetary system. Low values of involvement levels were obtained in all countries in the global transnational production subsystem, which indicated a lack of development of the transnational production of the EAEC countries. Low values of involvement levels were received in the world monetary subsystem in all countries, except Russia, showed the average level of involvement, due to the presence of the share of the ruble in the total turnover of the global foreign exchange market for currency pairs in the year 2016. A set of the best values were obtained in the common information space subsystem, where all the countries except Kyrgyzstan, showed an average level due to criterion – percentage of individuals using the internet, instead of the criterion, reflecting the development of infrastructural capacity. Russia was characterized by a higher level, and Kyrgyzstan, by a lower level of involvement in the global economy compared to other countries of the EAEC.